A study of the modification of Y-TZP and resin cement with titanium dioxide nanotubes - Chaves, Ana Paula Rodrigues de Magalhães (2017)
Titanium dioxide nanotubes (TiO2) have been applied to enhance the mechanical properties of dental materials. Yttria-stabilized tetragonal zirconia polycrystals (Y-TZP) has been increasingly used in dentistry. Aside from its optimal clinical results, Y-TZP is prone to failures related to insufficient thickness of the fixed prostheses connector and debonding due to its difficult adhesion. The purpose of this study is to evaluate the effect of the addition of different concentrations of TiO2 to YTZP in its mechanical properties and microstructure, and also to evaluate the influence of these nanotubes on the bond strength when added to the ceramic or to the resin cement. To evaluate that, the described purposes were divided in two different papers. Paper 1 describes the tests of biaxial flexural strength, fractography qualitative analysis in scanning electron microscopy (SEM), microstructure evaluation in field emission-SEM and X-ray diffraction. Groups evaluated were commercial YTZP (Ivoclar Vivadent) (ZC) and an experimental Y-TZP with different blends of nanotubes [0 (Z0), 1 (Z1), 2 (Z2), and 5% (Z5), in volume]. In paper 2 shear bond strength test is described. It was carried out with the following groups: commercial YTZP (Ivoclar Vivadent) (ZC) and an experimental Y-TZP with different blends of nanotubes [0 (Z0), 1 (Z1), 2 (Z2), and 5% (Z5), in volume] bonded to the resin cement Panavia F2.0; and commercial Y-TZP bonded to resin cement RelyX U200 added with different blends of nanotubes in two curing methods dual-cured [0 (DC), 0.3 (D03), 0.6 (D06) and 0.9% (D09) of nanotubes in weigth] or self-cured [0 (SC), 0.3 (S03), 0.6 (S06) and 0.9% (S09) of nanotubes in weigth]. Values of flexural strength and shear bond strength were subjected to ANOVA and Tukey (=0.05). Flexural strength values were also subjected to Weibull statistics. Grain sizes values were subjected to Kruskal-Wallis and Dunn tests (=0.05). The flexural strength results were: ZC 896.73±122.70; Z0 577.67±62.26; Z1 477.32±75.65; Z2 492.25±63.19; Z5 437.18±53.55. The Weibull modulus results found were: ZC 7.9; Z0 11.2, Z1 8.7; Z2 8.1; Z5 9.3. Results showed that experimental Y-TZP presented lower flexural strength values than commercial one, but the first presented better Weibull modulus (m). Experimental Y-TZP also presented good microstructure, comparable to commercial Y-TZP, with very similar grain sizes. Nanotubes addition to Y-TZP led to lower flexural strength, although higher m than commercial ceramic. Pores containing Ti were observed in Y-TZP as the nanotubes concentration raised. Shear bond strength results found were, from higher to lower values: Z5 6.46±3.36; DC 6.17±0.87; D03 5.74±1.70; S03 5.73±1.71; Z1 5.16±2.62; D06 4.82±1.06; D09 4.75±1.43; SC 4.73±1.43; S09 4.61±0.85; S06 4.51±1.87; ZC 3.70±1.82; Z0 -3.33±2.05; Z2 2.94±1.38. Shear bond strength was also influenced by nanotubes addition, either in the ceramic or in the cement, although not linearly. Y-TZP added of 5% of TiO2 nanotubes presented the highest bond strength, although with no significant difference from most groups. Group Z1 was probably the group that presented the best combination of flexural strength, m, microstructure and bond strength. More studies of other properties could be carried out with this group.